STRATEGI PENGEMBANGAN BUDIDAYA IKAN DI KAMPUNG IWAK KELURAHAN MENTAOS KOTA BANJARBARU - Hutauruk, Sanggam B Bomerson; Fauzana, Noor Arida; Slamat , Slamat; Agusliani, Erma (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The internal and external factors summarized can be the basis for determining a more focused strategy for developing fish cultivation in the Mentaos iwak village, Banjarbaru City, which has so far been untouched. The research aims to analyze the strategy for developing fish cultivation in Kampung Iwak Mentaos Village, Banjarbaru City. The research was carried out for 5 months, with data collection taking place in Kampung Iwak, Mentaos Village, Banjarbaru City, South Kalimantan Province. The type of data in this research uses primary data and secondary data. The data analysis technique to answer the objective is to describe the profile of fish cultivation that has been carried out in the Kampung iwak Mentaos village, descriptive analysis is used, to formulate a strategy for developing fish cultivation in the Kampung iwak Mentaos village, SWOT analysis is used. The profile of fish cultivation that has been carried out in the Mentaos iwak village was founded in 1992. The age of the cultivators ranges from 35 years to >57 years. The area of Kampung Iwak Mentaos Village is ± 47 Ha / 476.1396 m2, quantitatively there are around 205 pond plots consisting of nursery ponds, enlargement ponds and mixed ponds (between nursery and enlargement). Pool area starts from 200m2 to >1000m2. Types of fish that are widely cultivated in iwak villages include tilapia, gourami, catfish and other freshwater fish. The strategy for developing fish cultivation in Kampung iwak, Mentaos village is based on quadrant < 1, which is a very profitable situation. The main strategy for fish cultivation in Kampung Iwak, Mentaos Village, Mentaos Subdistrict, is to become an area with a fisheries tourism attraction which is the basis of strength so that it can take advantage of existing opportunities.